2019
DOI: 10.3390/genes10121000
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Distribution, Expression and Function Analysis of the U-Box Gene Family in Brassica oleracea L.

Abstract: The plant U-box (PUB) protein family plays an important role in plant growth and development. The U-box gene family has been well studied in Arabidopsis thaliana, Brassica rapa, rice, etc., but there have been no systematic studies in Brassica oleracea. In this study, we performed genome-wide identification and evolutionary analysis of the U-box protein family of B. oleracea. Firstly, based on the Brassica database (BRAD) and the Bolbase database, 99 Brassica oleracea PUB genes were identified and divided into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 73 publications
(66 reference statements)
3
12
0
Order By: Relevance
“…Most members of the U-box gene family are ligases, mediating the ubiquitination modification of protein, which enables ubiquitin to be combined with substrates to manipulate various protein activities ( Azevedo et al, 2001 ; Monaghan et al, 2009 ; Wang et al, 2015 ; You and He, 2016 ; Qin et al, 2020 ). It has been reported that the expression of U-box genes can affect their functions both in plant development and stress conditions ( Hu et al, 2018 , 2019 ; Lu et al, 2020 ; Sharma and Taganna, 2020 ; Wang J. et al, 2020 ; Wang N. et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most members of the U-box gene family are ligases, mediating the ubiquitination modification of protein, which enables ubiquitin to be combined with substrates to manipulate various protein activities ( Azevedo et al, 2001 ; Monaghan et al, 2009 ; Wang et al, 2015 ; You and He, 2016 ; Qin et al, 2020 ). It has been reported that the expression of U-box genes can affect their functions both in plant development and stress conditions ( Hu et al, 2018 , 2019 ; Lu et al, 2020 ; Sharma and Taganna, 2020 ; Wang J. et al, 2020 ; Wang N. et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…AtPUB11 degrades AtLRR1 (LEUCINE RICH REPEAT PROTEIN 1) and Atkin7 (KINASE 7), and negatively regulates ABA-mediated drought tolerance in Arabidopsis thaliana ( Chen X. X. et al, 2020 ). However, U-box genes have important value for plant resistance, and they have been identified in rice ( Oryza sativa ), tomato ( Solanum lycopersicum ), apple ( Malus domestica ), banana ( Musa nana ), soybean ( Glycine max ), Chinese cabbage ( Brassica rapa ), cotton ( Gossypium hirsutum ), and cabbage ( Brassica oleracea ) ( Azevedo et al, 2001 ; Li et al, 2009 ; Wang et al, 2015 , Wang J. et al, 2020 ; Wang K. L. et al, 2020 ; Hu et al, 2018 , 2019 ; Sharma and Taganna, 2020 ). However, comprehensive genome-wide identification of U-box genes in sorghum has not been performed, and expression characteristics have not been analyzed.…”
Section: Introductionmentioning
confidence: 99%
“…ARC1 is a typical E3 ubiquitin ligase in B. oleracea self-incompatibility, which plays an important role in the signal process of selfincompatibility. At the same time, PUB protein and ARC1 belong to E3 ubiquitin ligase, which may lead to self-incompatibility by negative regulation of pollen germination or interaction with SRK during B. oleracea self-incompatibility [53][54][55]. E3 ubiquitin ligase plays an important role in B. oleracea self-incompatibility, and BoGAPC may be involved in B. oleracea self-incompatibility by interacting with E3 ubiquitin ligase or producing other biological stress responses.…”
Section: Replication and Evolution Of Gapdh Gene In B Oleraceamentioning
confidence: 99%
“…The 2000-bp sequences of sunflower PM H + -ATPase gene promoters were extracted from the H. annuus L. genome database [29]. The promoter Cis-acting elements were detected and identified using the PLACE database [36]. The distribution of salt stress-related Cis-acting elements were visualized by GSDS 2.0 [34].…”
Section: Cis-acting Elements Analysis Of Pm H + -Atpase Genes Promotementioning
confidence: 99%